The Smart Glove Malaysian Sign Language Translator - Mohamad, Nor Syafiq; Lias, Jais (Evolution in Electrical and Electronic Engineering, 2021)
The medium for deaf and mute people to communicate is by sign language that using mostly hand gesture to make the sign. There are somewhere between 138 and 300 different types of sign language used throughout the world today. In Malaysia there were not much people can understand the sign language. Based on the research negative attitudes of Malaysian toward Children with disabilities (CWDs) have been disclosed recently. Azizan (2015, July 5) reported that low opportunities are given to CWDs and people with disabilities (PWDs) when enroll to schools and universities. The lack of communication between normal and these special people is one of the factor that make people lack of awareness. Smart glove MSL translation examines the possibility of recognizing sign language gestures using Flex sensor and explores their use in Sign Language recognition. This project focused on one hand gesture sign language that commonly used in a daily life.   By using the 2 main sensor which is flex sensors and gyro sensor the parameter of some basic hand gesture movement can be measured. All the sensor is connected to the ESP32 which is have a feature to connect the project hardware to application software designed via Bluetooth or Wi-Fi. An experiment is carried out to measure the accuracy of the project, using 3 different people to use the glove and the data is recorded. The average accuracy of the project is 86.47% for every 11 sign gestures data collected. The output of this project is in form of a voice, text and picture that will be displayed on the smartphone screen